Konstruksi Realitas Sosial atas Peristiwa Ambruknya Jembatan Kutai Kartanegara - Masri Sareb Putra (Ultimacomm: Jurnal Ilmu Komunikasi, 2011)
To be truthful, human being is incapable to grasp and see reality as it is. Knowing this incapability, human being is only capable to create the so-called “perceived reality,” that is, reality as already perceived. This perceived reality is the result of social construction of reality, built within the limited horizon of a person. This kind of social construction of reality is on display by the media, regarding the news about the fall of Kutai Kartanegara bridge. Keywords: realitas, konstruksi, masyarakat, individu, media